Ascetical Theology of Sport - McGavin, P. A. 1943- (2022)
This paper examines the document of Giving the Best of Yourself by the Dicastery for Laity, Family and Life, and presents an appreciation of the document and builds a case for sport as a practice of ascetical theology approached in terms of ‘everyday holiness’. Sports are argued as bringing together discipline and joy, and aesthetics and asceticism. The importance of the mean in diverting pathologies in sport is argued. Appreciation of sports is set in contexts of holistic lifestyles for its transformational and sanctification aspects to be appreciated. Sports are presented as beneficial life-long activity, and not simply for the young and physically advantaged. The article brings sport to theological articulation that is incarnational and christological and that leads to culturally situated implementations as applied ascetical theology.
Keywords: incarnational theology; Evangelium gaudium; holistic lifestyle; Giving the Best of Yourself; Sports; Ascetical Theology